2016
DOI: 10.21608/ajas.2016.2052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some Treatments on Chemical Composition and Quality Properties of Saidy Date Fruit (Phoenix dactylifera L.) During Storage

Abstract: This study was conducted out to improve the quality and the shelf-life of Saidy date variety during storage period for 12 months at room temperature using packing under vacuum, drying and irradiation (1KGy) treatments. Results showed that packing under vacuum is more effective for controlling the insect infestation (3.85%) followed by the irradiated (11.12%), dried (12.11%). While, the control sample recorded 17.24%, at the end of storage time (12 months). The moisture content of the control date sample decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Siwi had the highest moisture content, while Ajwa had the lowest, with no significant difference between Sukkari and the other two varieties. The findings are like those previously reported for dates from Saudi Arabia [ 47 ] and in agreement with those founded by Ramadan et al and Selim et al for Egyptian Siwi dates [ 48 , 49 ], but higher than those reported by Perveen and Bokahri for Sukkari dates [ 38 ].…”
Section: Resultssupporting
confidence: 93%
“…Siwi had the highest moisture content, while Ajwa had the lowest, with no significant difference between Sukkari and the other two varieties. The findings are like those previously reported for dates from Saudi Arabia [ 47 ] and in agreement with those founded by Ramadan et al and Selim et al for Egyptian Siwi dates [ 48 , 49 ], but higher than those reported by Perveen and Bokahri for Sukkari dates [ 38 ].…”
Section: Resultssupporting
confidence: 93%